Електрофільна гетероциклізація алкеніл- та алкінілфункціоналізованих азинів в синтезі поліядерних гетероциклічних систем - Онисько, Михайло Юрійович (ДВНЗ «Ужгородський національний університет», 2020)
Дисертаційна робота присвячена з’ясуванню закономірностей реакцій електрофільної гетероциклізації алкеніл(алкініл)-функціоналізованих азинів під дією галогенів, халькогентетрагалогенідів та арилтелуртригалогенідів. Метою дисертаційного дослідження є розробка зручних методів конструювання азоло(азино)анельованих азинів та діазинів та дослідження їхніх хімічних, біологічних, фізичних властивостей. Встановлені закономірності анелювання додаткового нітрогеновмісного гетроциклу до остова азину чи діазину у реакції електрофільної гетероциклізації під дією галогенів, залежно від наявності і природи замісника в алільному фрагменті алкенільних похідних азинів, положення алкенільного замісника. Виявлено, що при галоциклізації термінально незаміщених алкенілтіо(оксо, аміно, селено)азинів з високими виходами утворюються тригалогеніди тіазолоазинів. Введення двох метильних замісників до алілу не впливає на регіонапрямленість процесу циклізації. Натомість, у випадку фенільного чи метильного замісника в алілі змінюється напрямок циклізації і утворюються тіазиноазиній тригалогеніди. Запропоновано імовірні механізми перебігу реакцій циклізації термінальних та інтернальних алільних похідних азинів. Доведено мінімальний вплив природи екзоциклічного халькогену в азині на регіонаправленість процесу електрофільної циклізації. Регіохімія процесу електрофільної циклізації алкеніл(алкініл)-функціоналізованих азинів під дією халькогентетрагалогенідів залежить від природи базового азину, виду і положення алкенільного замісника, природи халькогену електрофільного реагента, розчинника та умов проведення реакції. Встановлено, що циклізація алілтіозаміщених піразоло[3,4-d]піримідинів з тетрабромідом селену приводить до утворення гетероциклів з ендо- та екзоциклічним атомом селену. Регіоселективність процесу залежить від полярності розчинника та виду замісника в положенні 1 піразолу. Алільний тіоетер хіноліну при дії тетраброміду селену циклізується з анелюванням тільки тіаселеназинового кільця, що доведено хімічними перетвореннями. Регіоселективність процесу селенобромування цинамільного тіоетеру хінолін-3-карбальдегіду зменшується, що приводить до утворення суміші ізомерів селеновмісних гетероциклів з екзо- та ендоциклічним селеном. Введення двох метильних замісників до алільного фрагменту селеноетеру хіноліну підвищує селективність селенобромування з формуванням селеназолохіноліній броміду. Процес телуроіндукованої електрофільної циклізації алільних та пропаргільних тіо(селено)етерів є регіоселективний, що приводить до утворення біологічно активних телуровмісних тіазоло(селеназоло)хіноілінів. Запропоновано механізм халькогенгетероциклізації, що залежить від первинної атаки електрофільного реагента на альтернативні нуклеофільні центри алкенілфункціоналізованого азину. Зміна положення алкенільного замісника від сульфура до нітрогену азину підвищує регіоселективність процесу і приводить до утворення тригалогенхалькогенометилзаміщених хіназолінів незалежно від природи халькогену. Виявлено, що телуроіндукована циклізація N-алкенільних 2(6)-тіоксодіазинів п-алкоксифенілтелуртрихлоридами регіоселективно утворює лінійно конденсовані тіазоліновмісні гетероцикли піримідинового ряду. Знайдені закономірності електрофільної внутрішньомолекулярної циклізації 2-S-алкенільних піримідин-4-онів під дією п-алкоксифенілтелуртрихлоридів і доведено, що напрямок гетероциклізації залежить від наявності замісника в положенні 3 піримідинового циклу. Стереоселективність арилтелурохлорування 2-S-пропаргільних піримідин-4-онів залежить від структури субстрату та регіохімії гетероциклізації. Виявлена висока антибактеріальна, протигрибкова та антиплазмолітична активність телурофункціоналізованих поліядерних азинів. Диссертационная работа посвящена выяснению закономерностей реакций электрофильной гетероциклизации алкенил(алкинил)- функционализированных азинов под действием галогенов, халькогентетрагалогенидов и арилтеллуртригалогенидов. Целью диссертационного исследования является разработка методов конструирования азоло(азино)аннелированных азинов и исследование их химических, биологических и физических свойств. Установлены закономерности аннелирования азотсодержащего гетроцикла к каркасу азина в реакции электрофильной гетероциклизации под действием галогенов, в зависимости от наличия и природы заместителя в аллильном фрагменте алкенильных производных азинов, положения алкенильного заместителя. Найдено, что при галоциклизации терминально незамещенных алкенилтио(оксо,амино,селено)азинов с высокими выходами образуются тригалогениды тиазолоазинов. Введение двух метильных заместителей в аллильный фрагмент не влияет на регионаправленность процесса циклизации. В то же время, в случае фенильного или метильного заместителя в аллиле изменяется направление циклизации и получены тиазиноазиний тригалогениды. Предложены возможные механизмы реакций циклизации терминальных и интернальных аллильных производных азинов. Доказано минимальное влияние природы экзоциклического халькогена в азине на регионаправленность процесса электрофильной циклизации. Региохимия процесса электрофильной циклизации алкенил(алкинил)-функционализированных азинов под действием халькогентетрагалогенидов зависит от природы базового азина, вида и положения алкенильного заместителя, природы халькогена электрофильного реагента, растворителя и условий реакции. Доказано, что циклизация аллилтиозамещенных пиразоло[3,4-d]пиримидинов с тетрабромидом селена приводит к образованию гетероциклов с эндо- и экзоциклическим атомом селена. Региоселективность процесса зависит от полярности растворителя и вида заместителя в положении 1 пиразола. Аллильный тиоэфир хинолина при действии тетрабромида селена циклизуется с аннелированием тиаселеназинового кольца, что доказано химическими превращениями. Региоселективность процесса селенобромирования циннамильного тиоэфира хинолин-3-карбальдегида уменшается, что приводит к образованию смеси изомеров селеносодержащих гетероциклов с экзо- и эндоциклическим селеном. Введение двух метильных заместителей в аллильный фрагмент селеноэфира хинолина повышает селективность селенобромирования с образованием селеназолохинолиний бромида. Процесс теллуриндуцированной электрофильной циклизации аллильных и пропаргильных тио(селено)эфиров региоселективен, что приводит к образованию биологически активных теллурсодержащих тиазоло(селеназоло)хинолинов. Предложен механизм халькогенгетероциклизации, который зависит от первичной атаки электрофильного реагента на альтернативные нуклеофильные центры алкенилфункционализированного азина. Изменение положения алкенильного заместителя от серы к азоту азина повышает региоселективность процесса и приводит к образованию тригалогенхалькогенометилзамещенных хиназолинов независимо от природы халькогена. Доказано, что теллуроиндуцированная циклизация N-алкенильных 2(6)-тиоксодиазинов п-алкоксифенилтеллуртрихлоридами региоселективно образует линейно конденсированные тиазолиносодержащие гетероциклы пиримидинового ряда. Найдены закономерности электрофильной внутримолекулярной циклизации 2-S-алкенильных пиримидин-4-онов под действием п-алкоксифенилтеллуртрихлоридов и доказано, что направление гетероциклизации зависити от присутствия заместителя в положении 3 пиримидинового цикла. Стереоселективность арилтеллурхлорирования 2-S-пропаргильных пиримидин-4-онов зависити от структуры субстрата и региохимии гетероциклизации. Найдена высокая антибактериальная, антигрибковая и антиплазмолитическая активность теллурофункционализированных полиядерных азинов. The dissertation is devoted to the establishment of the regularities of electrophilic heterocyclization reactions of alkenyl (alkynyl)-functionalized azines under the action of halogens, chalcogen tetrahalides, and aryltellurium trihalides. The purpose of the dissertation research is to develop convenient methods for constructing azolo-(azino-)annelated azines and diazines and to study their chemical, biological and physical properties. Regularities of an annelation of an additional nitrogen-containing heterocycle to the azine or diazine backbone in the electrophilic heterocyclization reaction under the action of halogens, depending on the presence and nature of the substituent in the allyl fragment of alkenyl derivatives of azines, and on the position of the alkenyl substituent, were established. It was found that halocyclization of terminally unsubstituted alkenylthio(oxo, amino, seleno) azines with high yields produce thiazoloazine trihalides. The introduction of two methyl substituents to allyl does not affect the regiodirection of the cyclization process. Instead, in the case of a phenyl or methyl substituent in the allyl, the direction of cyclization changes and thiazinoazine trihalides are formed. Probable mechanisms of cyclization reactions of terminal and internal allylic derivatives of azines are offered. The minimal influence of the nature of exocyclic chalcogen in azine on the regiodirection of the electrophilic cyclization process is proved. The detected anisochrony of NMR signals of ortho- and meta-protons and carbons of the N-phenyl substituent in tricyclic thiazolino(thiazino)pyrazolo[3,4-d]- and thiazolino(thiazino)pyrazolo[4,3-d]pyrimidinium trihalides is due to the inhibited rotation of phenyl. It was found that the halocyclization of propargyl thio-, oxo- and selenoethers of azines occurs regio- and stereoselectively and depends on the type and presence of substituents in azines. In order to search for new potentially biologically active compounds with pyrazolopyrimidine, quinoline and quinazoline cycles, the interaction of thio- and selenoethers of azines with tetrahalides of selenium and tellurium, which were used both as in the in situ reaction from chalcogen dioxide and hydrohalic acids and as pre-synthesized compounds, was investigated. The regiochemistry of the electrophilic cyclization process depends on the type and position of the alkenyl substituent, the nature of the chalcogen of the electrophilic reagent, the solvent and the reaction conditions. It was found that the cyclization of allylthio-substituted pyrazolo[3,4-d]pyrimidines with selenium tetrabromide leads to the formation of heterocycles with endo- and exocyclic selenium atom. The regioselectivity of the process depends on the polarity of the solvent and the type of substituent in position 1 of the pyrazole moiety. Under the action of selenium tetrabromide, the allyl thioether of quinoline is cyclized with annelation of only the thiaselenazine ring, which is proved by chemical transformations. The regioselectivity of the selenium bromination process of cinnamyl thioether of quinoline-3-carbaldehyde decreases, which leads to the formation of a mixture of isomers of selenium-containing heterocycles with exo- and endocyclic selenium. The introduction of two methyl substituents to the allylic fragment of the quinoline selenoether increases the selectivity of selenobromination with the formation of selenazoloquinoline bromide. The process of tellurium-induced electrophilic cyclization of allyl and propargyl thio (seleno) ethers is regioselective, which leads to the formation of biologically active tellurium-containing thiazolo (selenazolo) quinolines. The mechanism of chalcogen-heterocyclization depends on the primary attack of the electrophilic reagent on alternative nucleophilic centers of alkenyl-functionalized azine. Changing the position of the alkenyl substituent in azines from sulfur to nitrogen increases the regioselectivity of the process and leads to the formation of trihalogen chalcogenomethyl-substituted quinazolines, regardless of the nature of the chalcogen. It was found that tellurium-induced cyclization of N-alkenyl 2(6)-thioxodiazines by p-alkoxyphenyltellurium trichloride regioselectively forms linearly condensed thiazoline-containing heterocycles of the pyrimidine series. The regularities of electrophilic intramolecular cyclization of 2-S-alkenyl pyrimidin-4-ones under the action of p-alkoxyphenyltellurium trichlorides are found and it is proved that the direction of heterocyclization depends on the presence of a substituent in position 3 of the pyrimidine cycle. The stereoselectivity of aryltellurochlorination of 2-S-propargyl pyrimidin-4-ones depends on the structure of the substrate and the regiochemistry of heterocyclization. The influence of the halogen’s nature in halogen-containing electrophilic reagents on the process of electrophilic heterocyclization of alkenyl-functionalized azines has been studied. The possibility of using chlorine as an electrophilic reagent in such reactions is indicated. It is shown that the nature of halogen in chalcogen halogen-containing electrophilic agents affects only the yields of cyclization products. High antibacterial, antifungal, and antiplasmolytic activity of telluro-functionalized polynuclear azines were revealed.
Электрофильная гетероциклизация алкенил- и алкинилфункционализированных азинов в синтезе полиядерных гетероциклических систем
Electrophilic heterocyclization of alkenyl- and alkynyl-functionalized azines in a synthesis of polynuclear heterocyclic systems
Keywords: піразоло[3,4-d]піримідин; хінолін-3-карбальдегід; тієно[2,3-d]піримідин; хіназолін; електрофільна гетероциклізація; тетрагалогеніди селену і телуру; п-алкоксифенілтелуртрихлорид; регіоселективність; стереоселективність; тіазолоазин; тіазиноазин; антимікробна та антиплазмолітична активність; пиразоло[3,4-d]пиримидин; хинолин-3-карбальдегид; тиено[2,3-d]пиримидин; хиназолин; электрофильная гетероциклизация; тетрагалогениды селена и теллура; п-алкоксифенилтеллуртрихлорид; региоселективность; стереоселективность; тиазолоазин; тиазиноазин; антимикробная и антиплазмолитическая активность; pyrazolo[3,4-d]pyrimidine; quinoline-3-carbaldehyde; thieno[2,3-d]pyrimidine; quinazoline; electrophilic heterocyclization; tetrahalides of selenium and tellurium; p-alkoxyphenyltellurium trichloride; regioselectivity; stereoselectivity; thiazoloazine; thiazinoazine; antibacterial and antiplasmolytic activity; 547.789+547.859.1+547.778.3+547.831.8